Aspirin with or without Clopidogrel after Transcatheter Aortic-Valve Implantation - Brouwer, Jorn; Nijenhuis, Vincent J; Delewi, Ronak; Hermanides, Renicus S; Holvoet, Wouter; Dubois, Christophe L F; Frambach, Peter; De Bruyne, Bernard; van Houwelingen, Gert K; Van Der Heyden, Jan A S; Toušek, Petr; van der Kley, Frank; et al. (The New England journal of medicine, 2020)
BACKGROUND: The effect of single as compared with dual antiplatelet treatment on bleeding and thromboembolic events after transcatheter aortic-valve implantation (TAVI) in patients who do not have an indication for long-term anticoagulation has not been well studied. METHODS: In a randomized, controlled trial, we assigned a subgroup of patients who were undergoing TAVI and did not have an indication for long-term anticoagulation, in a 1:1 ratio, to receive aspirin alone or aspirin plus clopidogrel for 3 months. The two primary outcomes were all bleeding (including minor, major, and life-threatening or disabling bleeding) and non-procedure-related bleeding over a period of 12 months. Most bleeding at the TAVI puncture site was counted as non-procedure-related. The two secondary outcomes were a composite of death from cardiovascular causes, non-procedure-related bleeding, stroke, or myocardial infarction (secondary composite 1) and a composite of death from cardiovascular causes, ischemic stroke, or myocardial infarction (secondary composite 2) at 1 year, with both outcomes tested sequentially for noninferiority (noninferiority margin, 7.5 percentage points) and superiority. RESULTS: A total of 331 patients were assigned to receive aspirin alone and 334 were assigned to receive aspirin plus clopidogrel. A bleeding event occurred in 50 patients (15.1%) receiving aspirin alone and in 89 (26.6%) receiving aspirin plus clopidogrel (risk ratio, 0.57; 95% confidence interval [CI], 0.42 to 0.77; P = 0.001). Non-procedure-related bleeding occurred in 50 patients (15.1%) and 83 patients (24.9%), respectively (risk ratio, 0.61; 95% CI, 0.44 to 0.83; P = 0.005). A secondary composite 1 event occurred in 76 patients (23.0%) receiving aspirin alone and in 104 (31.1%) receiving aspirin plus clopidogrel (difference, -8.2 percentage points; 95% CI for noninferiority, -14.9 to -1.5; P<0.001; risk ratio, 0.74; 95% CI for superiority, 0.57 to 0.95; P = 0.04). A secondary composite 2 event occurred in 32 patients (9.7%) and 33 patients (9.9%), respectively (difference, -0.2 percentage points; 95% CI for noninferiority, -4.7 to 4.3; P = 0.004; risk ratio, 0.98; 95% CI for superiority, 0.62 to 1.55; P = 0.93). A total of 44 patients (13.3%) and 32 (9.6%), respectively, received oral anticoagulation during the trial. CONCLUSIONS: Among patients undergoing TAVI who did not have an indication for oral anticoagulation, the incidence of bleeding and the composite of bleeding or thromboembolic events at 1 year were significantly less frequent with aspirin than with aspirin plus clopidogrel administered for 3 months. (Funded by the Netherlands Organization for Health Research and Development; POPular TAVI EU Clinical Trials Register number, 2013-003125-28; ClinicalTrials.gov number, NCT02247128.).
Keywords: Hemorrhage; kardiovaskulární nemoci; Humans; klopidogrel; Postoperative Period; Female; Aged; inhibitory agregace trombocytů; senioři; lidé; Administration, Oral; Thrombosis; Transcatheter Aortic Valve Replacement; transkatetrální implantace aortální chlopně; ženské pohlaví; Cardiovascular Diseases; Male; incidence; Incidence; Aged, 80 and over; Aspirin; trombóza; senioři nad 80 let; krvácení; Clopidogrel; aplikace orální; mužské pohlaví; pooperační období; kombinovaná farmakoterapie; Platelet Aggregation Inhibitors; Drug Therapy, Combination